2016
DOI: 10.1039/c6lc00769d
|View full text |Cite
|
Sign up to set email alerts
|

Versatile, cell and chip friendly method to gel alginate in microfluidic devices

Abstract: Alginate is used extensively in microfluidic devices to produce discreet beads or fibres at the microscale. Such structures may be used to encapsulate sensitive cargoes such as cells and biomolecules. On chip gelation of alginate represents a significant challenge since gelling kinetics or physicochemical conditions are not biocompatible. Here we present a new method that offers a hitherto unprecedented level of control over the gelling kinetics and pH applied to the encapsulation of a variety of cells in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 58 publications
0
79
0
1
Order By: Relevance
“…A more rigorous analysis of the application of CLEX to the microencapsulation of both eukaryotic and prokaryotic cells is described in detail elsewhere. 29 By way of demonstration, CLEX was also applied to form larger scale bulk gels by casting (Fig 4B) into an injection mould using a dual syringe to deliver equal volumes of alginate solution. A homogenous, bubble free gel was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…A more rigorous analysis of the application of CLEX to the microencapsulation of both eukaryotic and prokaryotic cells is described in detail elsewhere. 29 By way of demonstration, CLEX was also applied to form larger scale bulk gels by casting (Fig 4B) into an injection mould using a dual syringe to deliver equal volumes of alginate solution. A homogenous, bubble free gel was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Although the availability of binding sites for cells is critical for cell attachment and function, the bulk properties of hydrogels play an equally important role. Alginate is widely used as a platform to study the effect of mechanical cues because the gelation [31,32], swelling ratio [33], crosslinking density, and resultant moduli [34] can be easily tuned by calcium ion concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In these techniques, the introduction of the spacer flow was necessary, as it modulates the high gelation speed of alginate. Another interesting approach was recently reported by Hati et al (2016), wherein an in-situ gelation method based on ion-exchange was reported, which was called competitive ligand exchange crosslinking. Two types of metal complexes-Ca-EDTA and Zn-EDDA-were used, which were individually introduced into aqueous solutions of Na-alg.…”
Section: Droplet Micro Uidics To Produce Alginate Particlesmentioning
confidence: 99%